Issues in resolution and build size scaling of additive manufacturing technologies - Weerasekera, Naveen; Cao, Siyua; Biswas, Agnimitra (Open Science Journal, 2022)
In this review, scaling issues in additive manufacturing (AM) processes are discussed based on multiple factors. Scaling issues arise mainly due to design and control of the AM system and also while attempting to achieve desired accuracy. Based on current AM systems available commercially, we identified scaling issues that can potentially challenge the build feasibility and accuracy while moving in geometrical and build resolution length scales. Inherent limitations of multiple AM processes are discussed based on these aspects and challenges while implementing these technologies in multiple length scales are identified through this work. Potential remedies for such scaling issues are also presented based on current progressing research in AM.